Exploring workforce confidence and patient experiences: A quantitative analysis - Katie Owens; Stephanie Keller (The Beryl Institute, 2018)
Confidence is recognized as one of the most influential factors to affect performance. Individual, leader, and team confidence play essential roles in achieving success and the absence of confidence has been connected with failure. While confidence is not a substitute for competency, it creates trusting relationships, empowerment, and resiliency to persevere when challenges arise. Objective: In this study, we examined workforce confidence in the patient experience and patient perceptions of their experience of care. Methods: We compared responses to the Patient-Centered Excellence Survey (PCES) from 41 United States hospitals, measuring workforce confidence in the patient experience provided, to patient's ratings of their experience through the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey. Results: Higher workforce confidence in the patient experience provided is related to higher patient ratings of their experience while lower workforce confidence is linked with lower patient ratings. Hospitals in the top 25% with workforce perceptions score 11.7% higher with HCAHPS Overall Rating than hospitals in the bottom 25%. Of the 10,945 workforce respondents to the PCES Overall Rating item, 24.2% rated their organization top box (9 or 10) versus 64.7% of patients rating top box. Senior leaders reported the highest degree of confidence in the patient experience, while staff and providers reported the lowest. Conclusion: Confidence is an important characteristic of the healthcare workforce. Building mastery of patient experience competencies holds promise to further elevate patient's perceptions of their care. Gaps in confidence should be addressed - especially among those with the most direct caregiver responsibilities.